Assessment of Burnout Among Canadian Pharmacists Working in Team-based Primary Care Settings - Hayley Bessette; Caitlin Chew; Anita Kapanen; Jillian Reardon; Jamie Yuen (University of Minnesota Libraries Publishing, 2020)
Background: Burnout syndrome is well-documented among healthcare professionals across various practice settings. There has been recent expansion of Canadian pharmacists into team-based primary care and burnout in this setting has not been assessed. Our objective was to assess workplace burnout and to identify factors that play a role in perpetuating or diminishing it. Method: An online survey to assess burnout was developed using the Maslach Burnout Inventory (MBI) tool and questions regarding pharmacist background and practice. Invitations to complete the survey were sent to Canadian pharmacists working in team-based primary care settings on November 26, 2019 via a national primary healthcare listserv. Results: A total of 31/433 completed responses were collected. The main analysis focused on the personal accomplishment (PA) domain as it had an adequate response rate. The PA domain had a median score of 5.0 (95% CI 4.69-5.22). We compared medians of the PA domain across different groups of each categorical variable. We found that the number of years working in primary care settings was positively associated with a higher PA domain score (p= 0.029). Discussion: PA was higher in pharmacists who have been practicing in a primary care setting for longer; however, burnout rates could not be properly assessed due to the limited response rate. Conclusion: This is the first study to assess burnout among Canadian team-based primary care pharmacists. Personal accomplishment was higher in those who have been practicing in a primary care setting for longer. Future studies should consider alternate methods to evaluate burnout in this population.   Article Type: Original Research